IMPLEMENTATION OF BASIC IMMUNIZATION PROGRAM AT THE HEALTH CENTER IN THE DISTRICT OF KEPULAUAN MERANTI BANDUL 2016 - - Kiswanto; - Marina (Sistem Informasi, 2017)
The basic program of immunization in infants is a condition of achieving complete primary immunization of all infants under one year of age. In 2015, the achievement of immunization programs in the clinic Pendulum Meranti Islands District by 40%, this condition is still below the target in each health center set 91% in 2015. This shows the obstacles in achieving the immunization program allegedly due to non-optimal management implementation of immunization health centers in the region of Pendulum. The purpose of this study is to analyze the management of immunization in health centers with respect to achieving basic immunization in infants at Puskesmas Pendulum. This study is a qualitative study aimed to analyze the implementation of management which includes P1 (Planning), P2 (Mobilization and Implementation) and P3 (Monitoring, Control and Assessment) in immunization programs in Puskesmas Pendulum. The results showed that the overall performance of the functions of management at the health center for immunization Pendulum still baik.Pengawasan against immunization activities khususnnya workshop is not routinely done every month. Knowledge and awareness among parents of infants to participate in immunization activities is still lacking. Supervision of the lack of supervision of immunization activities puskesmas head. There needs to be a shared commitment of the leadership and all officials immunization health centers health centers and implementing immunization to improve the implementation of management functions to increase the performance of health centers health centers especially immunization program to be achieved.